Marine algae of Perak Island, Jarak Island and the Sembilan Group of Islands in the Straits of Malacca - Phang, Siew-Moi; Lim, Phaik-Eem; Ooi, Jillian Lean Sim; Yeong, Hui-Yin; Ng, Woan-Shien; KÃ¼pper, Frithjof C. (Malaysian Journal of Science, 2008)
A preliminary checklist of marine algae from Pulau Jarak, Sembilan Group of Islands and Pulau Perak in the Straits of Malacca was compiled from two expeditions. The checklist of a total of 66 taxa, comprises one family of Cyanophyta with two genera and six taxa, seven families of Chlorophyta with 11 genera and 18 taxa, 12 families of Rhodophyta with 20 genera and 39 taxa, and two families of Phaeophyta with three genera and three taxa. One new record Lyngbya confervoides f. violacea is reported for the first time for Malaysia. The three islands have a low similarity in marine algal diversity. Satu senarai semak rintis alga marin dari Pulau Jarak, Kepulauan Sembilan dan Pulau Perak di Selat Melaka dari dua ekspedisi telah digabungkan. Senarai semak yang mengandungi sebanyak 66 taxa ini terdiri daripada satu famili Cyanophyta dengan dua genera dan enam taxa; tujuh famili Chlorophyta dengan 11 genera dan 18 taxa; 12 famili Rhodophyta dengan 20 genera and 39 taxa; serta dua famili Phaeophyta dengan tiga genera dan tiga taxa. Satu rekod baru Lyngbya confervoides f. violacea telah dilaporkan untuk kali pertama bagi Malaysia. Ketiga-tiga pulau ini mempunyai kesamaan yang rendah dalam kepelbagaian alga marin.